The ain impacts of the Lisbon Strategy on tobacco growing - Mislovics, Anita (Acta Agraria Debreceniensis, 2006)
The Lisbon Strategy of the EU promises a more competitive Europe with more and better workplaces, in addition to sustainability. Tobacco production is one of the most controversial industries of the agricultural sphere in the European Union. This crop is a „leader” of the world’s economic growth, a promoter of globalisation and has been an economic channel between America and Europe for more than 500 years. It is also a motor of technical development, due to its inducing effect on profitability and work efficiency. The tax competition of the states and the increase in consumption have become such a self-inducing system in which the increase of production created an increasing number of jobs, especially in tobacco growing, where the replacement of manual labour was much slower than the increase of the demand for raw material. The fact that smoking is becoming general should be handled as a social demand, though its health risks cannot be denied. However, the extreme objection to smoking cannot be accepted, especially not when it evokes social strains and concludes that people smoke because of tobacco production, al though the real situation is the opposite: People smoke in Europe, so the tobacco should be grown here, as is in our economic interest. There is a contradiction between the strategic objectives and the roles of the industry which should be ceased urgently. Al thong aim is the creation of jobs, stopping tobacco growing could result in unexpected agro-social disadvantages. Rejection of the industry’s sustainability questions the realization of the keystones of the strategy. Competitiveness, sustainability and social cohesion should be implemented as a unit of the strategy also in tobacco growing.